2003
DOI: 10.1017/s1355617703930128
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological assessment and telemedicine: A preliminary study examining the reliability of neuropsychology services performed via telecommunication

Abstract: Within the last decade, various applications of two-way audio-visual telecommunication have been implemented in the Norwegian health care system to facilitate the delivery of medical services to patients located in rural areas away from the hospitals. This technology may also be useful to extend neuropsychological services to underserved areas and thereby reduce the patients' travel time and costs. In the current study, a total of 12 visual, verbal and performance tests were administered face-to-face and via v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 21 publications
1
42
0
Order By: Relevance
“…Good agreement was found across most tests examined, with intraclass correlations ranging from .58 to .88. Together with other encouraging findings from the literature using various brief assessments in small groups (Harrell, Wilkins, Connor, & Chodosh, 2014; Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2000; Turner, Horner, VanKirk, Myrick, & Tuerk, 2012; Vestal et al, 2006), these results suggested that VTC-based neuropsychological assessment in older individuals with and without cognitive impairment was feasible and had promising reliability despite that no large-scale studies more definitively establishing reliability had been conducted. Consumer acceptability of VTC-based neuropsychological assessment has also been explored in a recent investigation, with results suggesting good acceptance of VTC-based testing among healthy and cognitively impaired older individuals (Parikh et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…Good agreement was found across most tests examined, with intraclass correlations ranging from .58 to .88. Together with other encouraging findings from the literature using various brief assessments in small groups (Harrell, Wilkins, Connor, & Chodosh, 2014; Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2000; Turner, Horner, VanKirk, Myrick, & Tuerk, 2012; Vestal et al, 2006), these results suggested that VTC-based neuropsychological assessment in older individuals with and without cognitive impairment was feasible and had promising reliability despite that no large-scale studies more definitively establishing reliability had been conducted. Consumer acceptability of VTC-based neuropsychological assessment has also been explored in a recent investigation, with results suggesting good acceptance of VTC-based testing among healthy and cognitively impaired older individuals (Parikh et al, 2013).…”
Section: Introductionmentioning
confidence: 75%
“…A crossover design was used in previous studies involving remote psychometric assessments. 19,20 Benefits of the crossover design include removing between-patient variation and requiring fewer participants. Participants were randomly assigned to one of two experimental groups: one-half of the participants were initially tested face to face, followed by a remotely administered test; the other half were tested in the opposite order.…”
Section: Methodsmentioning
confidence: 99%
“…Growing evidence suggests that teleneuropsychology shows good agreement with traditional in-person assessment (Jacobsen, Sprenger, Andersson, & Krogstad, 2003; Kirkwood, Peck, & Bennie, 2001; Hildebrand, Chow, Williams, et al, 2004; Loh, Ramesh, Maher, et al, 2004; Vestal, Smith-Olinde, Hutton, & Hart, 2006). A feasibility study of teleneuropsychology in older subjects with and without dementia found correlations between 0.5 and 0.8 on a brief battery of common neuropsychological tools administered in-person and via videoconference (Cullum, Weiner, Gehrmann, & Hynan, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite promising results supporting the feasibility and reliability of teleneuropsychology, there are few published studies regarding patient acceptability of this methodology, particularly in populations with cognitive impairment. Preliminary findings from telemental health studies involving teleneuropsychology have anecdotally noted good patient and clinician acceptability (Jacobsen et al, 2003; Ramos-Rios, Mateos, Lojo, et al, 2012; Vestal et al, 2006). In a study of dementia diagnosis in residential care veterans, Shores et al (2004) found that most patients preferred completing the evaluation via video teleconference rather than traveling to a clinic.…”
Section: Introductionmentioning
confidence: 99%